Soldier defections in Myanmar: Motivations and obstacles following the 2021 military coup - Helene Maria Kyed; Ah Lynn (Danish Institute for International Studies (DIIS), 2021)
Nine months after the 1 February 2021 military coup in Myanmar, an estimated 2,000 soldiers of the 300,000-350,000 strong Myanmar military, the Tatmadaw, had defected. This has occurred in the context of massive popular resistance to the coup, which the military leadership has tried to quell with large-scale arrests, killings of civilians and various forms of intimidation. Since the first defections in late February, resistance has shifted from being exclusively non-violent to waging a low intensity and defensive warfare against the Tatmadaw's troops. As a result, the gap between the civilian population and the armed forces has widened, with significant loses on both sides. Yet this trend has been challenged mainly by some of the younger, lower-ranking soldiers, who have joined 'the people's side'. Some defectors take part in the armed resistance, while others are actively engaged in campaigns to mobilise more soldiers to leave the army or to tacitly circumvent orders from within. Increasingly, these defector groups have been supported by the political opposition to the military. This report draws on the narratives of active defectors to analyse what has motivated soldiers to defect after the military coup, and to conversely understand what obstacles there are to an increased scale of defections. We argue that while moral concerns regarding the violence against civilians after the coup has been a strong motivating factor, defections are also driven by deep dissatisfaction with the internal workings of the military system that existed prior to the coup. The support mechanisms, exit options, and alternative visions of order proclaimed by the civilian opposition to the coup also play an increasingly important role and would likely be decisive in motivating more defections. Yet the obstacles to defection are also pertinent and are intrinsically woven into the fabric of the Tatmadaw's long tradition of nurturing cohesion and loyalty among its armed forces - e.g., through ideological programming, isolation, hierarchical patron-client relations and a stringent system of commands, rewards, and punishments. While defectors suggest that many more rank-and-file soldiers would desert or defect if they did not fear punishment and for their family's security, our analysis also points to the fundamental structural obstacles that likely inhibit the cultivation of wide-spread motivations to split from the Tatmadaw. This report offers insights into the increasingly strong conviction that the disintegration of the Tatmadaw through internal splits and large-scale mutinies will be decisive in reversing the coup and for bringing Myanmar onto a genuinely democratic path. So far in Myanmar, there are no clear signs of impending major military splits, but the defections that have occurred can be considered a significant, albeit mainly symbolic, blow to the Tatmadaw's internal coherence and stability.
Keywords: 300